The aryl hydrocarbon receptor-mediated and genotoxic effects of fractionated extract of standard reference diesel exhaust particle material in pulmonary, liver and prostate cells. Issue 3 (April 2015) - Pálková, Lenka; Vondráček, Jan; Trilecová, Lenka; Ciganek, Miroslav; Pěnčíková, Kateřina; Neča, Jiří; Milcová, Alena; Topinka, Jan; Machala, Miroslav
Highlights Fractionated extract of standard DEP reference material was a potent AhR inducer. Both PAHs and polar aromatic compounds contributed to the AhR activation. Polar aromatic compounds contributed more significantly to DNA adduct formation. Cell-specific differences in activation of DNA damage response were identified.